Preparation and application of phosphorylated Lotus root polysaccharide - YAN,You-Yu (2022)
Abstract In this study, we extracted lotus root polysaccharide (LRP) and synthesised phosphorylated lotus root polysaccharide (PLP) using response surface methodology (RSM). RSM analyses revealed that the optimal conditions for PLP synthesis were a reaction duration of 7 h, temperature of 70 °C and pH of 11.38. Under these conditions, the predicted degree of substitution (DS%) was determined to be 9.96%. The structure of the LRP1 was examined by ultraviolet (UV) spectroscopy scan, Fourier transform infrared spectroscopy (FTIR) and nuclear magnetic resonance (NMR) (1H and 13C). The monosaccharide composition of LRP1 was determined to be mannose (0.12%), ribose(0.18%), glucuronic acid(0.60%), galacturonic acid(0.09%), glucose(98.79%) and galactose(0.21%). The number average molecular weight (Mn) and the weight average molecular weight (Mw) of LRP1 were 10236 and 251783 g/mol. LRP1 exhibited high antioxidant activities in scavenging ABTS radicals, Superoxide anion radicals and Metal ion scavenging activity. PLP exhibited strong antioxidant activity in vitro. In addition, PLP inhibited Skov3 cancer cell proliferation and induced reactive oxygen species (ROS) production. Our data revealed that PLP is a promising natural antioxidant with potential value as a food supplement and for the treatment of cancer.